The Power of Fear in Prevention Campaigns: Evaluating the Effectiveness of Loss and Coping Appeals on Pickpocketing Prevention Behavior. - FRIEMEL, THOMAS N.; REICHOW, DENNIS (International Journal of Communication (19328036), 2021)
All over the globe, public transport operators face a high level of pickpocketing and the challenge to address this topic through communicative actions. However, little is known about the effectiveness of preventive messages. Informed by health communication theories and based on an online experiment (N = 1,938) with a between-subject design, we found that a loss appeal increased the motivation to protect against pickpocketing, while no difference was found between the coping appeal and the control group. As suggested by the extended parallel process model (EPPM), the structural equation model supports the hypothesized crucial role of fear in inducing protection motivation. However, in contrast to the theory, no differences were found for the processes induced by the different messages. Based on these findings, we discuss the power of fear in prevention campaigns and the opportunities and challenges it presents for campaign practices regarding pickpocketing and other topics of prevention behavior.